Porandra microphylla Y. Wan (Commelinaceae): A new distributional record for Vietnam - Chinh, Vu Tien; Phuong Anh, Tran Thi; Quang, Bui Hong; Cuong, Nguyen The (Academia Journal of Biology, 2016)
Porandra microphylla Y. Wan, is a newly recorded species for the flora of Vietnam. This species was collected from Lai Chau and Vinh Phuc province of the country. Morphologically, P. microphylla is closely related to Porandra scandens D.Y. Hong, but differs by its smaller and abaxially glabrous leaves and oblong or subglobose anthers.